KUALITAS PELAYANAN PUBLIK DALAM PENGURUSAN DOKUMEN PERTANAHAN DI KANTOR KECAMATAN TATANGA KOTA PALU - Hanifa Samsu, Abu (Katalogis, 2015)
This research aims at analyzing the quality of public service in land documents handling in Tatanga Distric Office, Palu City and the factors which influence. The informants of this research are 9 persons consist of 5 government employees and 4 people. This research uses a purposive sampling technique to select the informants. The techniques of the data collection are observations, interviews, and documentations. The result of this research indicates that the quality of public services in land documents handling in Tatanga District Office, Palu City is not maximal yet. It can be seen from the 5 indicators which become a benchmark in this research, they are: Responsiveness, Assurance, Tangible, Empathy and Reliability. There are only two indicators which properly fulfilled namely the response of the apparatus to the people who are in difficulty in handling land documents and empathy indicator which indicates that the district officers have treated the people rightfully, while the assurance, tangible and reliability indicators are in less maximal category. From several parameters used, like assurance indicator which has one of knowledge aspects, the apparatus of Tatanga is not satisfying yet. From the physical evidence indicator that has three aspects of handling support of land documents, the waiting room condition is not based on what people expect. While from the aspect of reliability which has right appointment of land document service completion is not proven yet.